Developing and implementing a self-monitoring toolkit for a coordinated multinational randomized acupuncture trial - Sylvia Baedorf Kassis; Weidong Lu; Sarah A. White; Im Hee Shin; Sung Hwan Park; Young Ju Jeong; Chang Yao; Jennifer Ligibel; Barbara E. Bierer (BMC, 2022)
Abstract Background In 2019, investigators from China, South Korea and the United States of America initiated a coordinated multinational trial. The trial included three parallel randomized studies with a planned pooled analysis of individual patient data, to test the effectiveness of acupuncture on hot flash-related symptoms in hormone receptor-positive breast cancer patients prescribed adjuvant endocrine therapy. Given the study's approach, there was no central coordinating center or data monitoring committee for the study, so a site performance self-monitoring toolkit was developed and implemented to support study teams in collecting and maintaining high-quality regulatory information, and consistent review of study data and documentation. Methods The site performance self-monitoring toolkit was created based on best practices related to post-approval quality assurance/quality improvement (QA/QI) procedures that support data quality. The toolkit included: (1) a binder of essential study management documents and related monitoring logs for sites to complete and maintain (herein called regulator binder), (2) a study start-up checklist, (3) a self-assessment study conduct and oversight checklist to be completed regularly, and (4) a study close-out checklist. In addition, a process of regular virtual meetings to discuss documentation progress coupled with periodic external remote review of completed logs and checklists provided accountability checks. Results Over the course of the study, the sites in China and South Korea completed the entirety of the site performance self-monitoring toolkit, and successfully submitted their completed materials for review. The process of implementing a self-monitoring toolkit in a multinational integrative medicine study is described qualitatively. Periodic external review of the completed toolkit materials revealed categories of findings. Written follow-up reports were provided to sites and discussion of the documents occurred via separate virtual meetings. Conclusions Site study team self-monitoring provides a feasible, consistent, and effective way to review the collection and maintenance of data and regulatory documentation for quality assessment in minimal risk clinical research studies and can augment formal study monitoring activities in higher risk studies. Iterative feedback and support appeared to drive a disciplined approach to maintaining regulatory document compliance and helped sustain investigator and study team engagement in the process. Trial registration ClinicalTrials.gov Identifier NCT03783546 (21/12/2018).